Exploring variable neighborhood search for automatic algorithm configuration - Pérez Cáceres, Leslie; Stützle, Thomas (Electronic notes in discrete mathematics, 2017)
Methods for automatic algorithm configuration integrate some search mechanism for generating candidate algorithm configurations and mechanisms for handling the stochasticity of the algorithm configuration problem. One popular algorithm configurator is ParamILS, which searches the configuration space using an iterated local search algorithm. In our research, we explore variable neighborhood search mechanisms as an alternative for the one-exchange neighborhood that is searched in the local search phase of ParamILS. In this article, we explore a reduced variable neighborhood search for automatic configuration. Our experimental results are promising and indicate directions for extending our work.